Analisis Nilai Moral Dan Gaya Bahasa Dalam Film Mungkin Esok Lusa Atau Nanti Karya Iwan Kurniawan - Rizal Asrofi (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
The film "Mungkin Esok Lusa" (The Day After Tomorrow or Later) is a cinematic work that represents the dynamics of human life in the face of uncertainty, waiting, and inner struggle. This study aims to describe the moral values and language style contained in the film. The method used is a qualitative descriptive-analytical approach, where data is obtained through observation of the dialogue, storyline, and interactions between the characters in the film. The results indicate that the film contains moral values such as patience, sincerity, responsibility, empathy, and optimism for the future. These values are conveyed implicitly through conflict and character development. Furthermore, the dominant language styles include reflective, metaphorical, realistic, and emotive, which serve to strengthen the delivery of the moral message and build emotional closeness with the audience. The conclusion of this study indicates that the film "Mungkin Esok Lusa" (The Day After Tomorrow or Later) has potential as a learning medium for character education and film literature studies because it is able to convey moral messages simply, deeply, and relevantly to the realities of society. Keywords: moral values, language style, film, character education, literary studiesthe sentence. Abstract is equipped with Keywords consisting of 3-5 words which become the core of abstraction description. Keywords word is bold. Keywords: content, formatting, article.